PLASMA PARAMETERS INDUCED BY LASER OF CADMIUM OXIDE - Ola abedallah manaty; M.J. Khalifa (Zien Journals, 2022)
We have examined the optical emission spectra of the plasma created by cadmium oxide (CdO). Liquid (ethanol alcohol) by pulsed laser ablation in liquid media. PLA in the 200-600 nm range at the fundamental wavelength (1064 nm) Nd: YAG laser's wavelength. The Boltzmann diagram method and the extended Stark line coil, respectively, were used to extract plasma parameters such as electron temperature and electron number density. For temperature and selection, these lines at 313.316 nm, 326.363 nm, 340.365 nm, 346.62 nm, 361.050 nm, 467.814 nm, 470.991 nm, 508.582 nm, 588.582 nm, 609.914 nm are used to calculate the temperature, as well as choose the O.I. line 643.847 nm to calculate the electron density. Density number and electron temperature change were studied as a function of laser power. The plasma frequency, Debye length, and Debye number were determined as the laser energy computed functions
Keywords: Optical Emission Spectra; Plasma; Laser; Parameters